Theoretical considerations on the pedagogical competencies of Imaging and Medical Radiophysics teachers - Fernando Machado Acuña; Geovanis Olivares Paizan; Marhyam Solano Pérez; Susel Moll Varela (Revista Información Científica)
Introduction: the permanent training of teachers constitutes a constant challenge for universities. Cuban medical education demands the development of pedagogical skills in correspondence with the global panorama. The teachers of the Imaging and Medical Radiophysics career lack pedagogical training in the undergraduate degree that guides them in the conduct of the educational teaching process.